(untitled) (Revista científica Olimpia, 2022)
The present investigation is based on a diagnosis that shows difficulties in the development of basic motor skills (walking, running, jumping, throwing and catching), in children between 4 and 5 years of age who do not attend the Pink Popular Council child care centers. la Bayamesa To contribute to the solution of this problem, the following objective is proposed: to propose motivational activities to develop the basic motor skills of children between 4 and 5 years of age, from the Educate Your Child Program, from the Rosa la Bayamesa Popular Council. To do this, from a population of 25 children, a sample of 15 was taken to whom diagnostic instruments were applied that corroborate the need for this type of activity based on their motor development.